2012
DOI: 10.1002/uog.11215
|View full text |Cite
|
Sign up to set email alerts
|

Axonal loss and cognitive deficits in term infants with normal umbilical artery Doppler born small‐for‐gestational age

Abstract: Objective To assess cognitive outcomes and structural changes in the central nervous system, the latter using a novel approach to examine changes in neuronal integrity of the optic nerve, in children at 5-6 1 / 2 years of age who were born small-for-gestational age (SGA)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
12
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 41 publications
5
12
0
Order By: Relevance
“…Furthermore, correlations between these brain disturbances and neurological performance have been reported [33], [35].The majority of earlier studies were conducted in early-onset IUGR. However recent evidence supports that late-onset IUGR have changes in the same direction, including differences in brain metabolism and microstructure [37] and signs of increased axonal loss at 5 years of age [38]. Along the same lines, in a previous study we reported differences in textural patterns on fetal brain MRI between term SGA and AGA fetuses [20].…”
Section: Discussionsupporting
confidence: 55%
“…Furthermore, correlations between these brain disturbances and neurological performance have been reported [33], [35].The majority of earlier studies were conducted in early-onset IUGR. However recent evidence supports that late-onset IUGR have changes in the same direction, including differences in brain metabolism and microstructure [37] and signs of increased axonal loss at 5 years of age [38]. Along the same lines, in a previous study we reported differences in textural patterns on fetal brain MRI between term SGA and AGA fetuses [20].…”
Section: Discussionsupporting
confidence: 55%
“…Our research group had previously reported changes in the retinal structure of children born SGA,9 10 15 both in ganglion cells and in their axons constituting the RNFL. The aim of the present study was to identify anomalies in SGA children with no neonatal adverse events, normal neurological assessment at birth and at inclusion in the study, and normal brain ultrasonography at neonatal period; and to evaluate whether retinal changes correlated with brain anomalies.…”
Section: Discussionmentioning
confidence: 95%
“…Our research group first reported thinning in the retinal nerve fibre layer (RNFL) and impaired performance intelligence scores in school-age children born SGA due to exposition to chronic hypoxia and undernutrition in fetal life 9 10. It has recently been reported in early preterm infants that thinner RNFL may relate to brain structure and neurodevelopment 11.…”
Section: Introductionmentioning
confidence: 99%
“…However, inconsistent results with regard to birth weight and GA have been previously reported 1–3 6 8. Most authors investigated the effects of birth weight and GA independently, with some authors able to show that RNFLT decreases also in term10 and late-preterm infants11 with a birth weight below the 10th percentile. Accordingly, Pueyo et al 6 hypothesised that RNFL damage could be caused by low birth weight in preterm and full-term infants.…”
Section: Discussionmentioning
confidence: 99%